Gestión de residuos sólidos urbanos y factores de desperdicio de alimentos en Quito (Tema Central) - Oña Serrano, Xavier (2024)
The organic composition of 65 % of urban solid waste of the Metropolitan District of Quito originates from food waste, which has negative environmental effects. The purpose of this study was to evaluate the factors related to food waste in homes in the capital and characterize urban solid waste management. The study is quantitative and exploratory. An association analysis was performed for the main categorical variables through calculation of statistical chi squared and an assessment of polychoric relation. A descriptive and multi-scale statistical analyses were performed for focus of the social metabolism to characterize waste management. A noteworthy element was the relation between expenses for purchase of food and non-alcoholic beverages in the last month-household income in the last month (p value < 5 %). Between 2012-2021, the most representative median for waste generation corresponded to the Eugenio Espejo administration, with 141470 t/ year, with a metabolic waste rate of 2.45E-05 (t/year). On the other hand, the Tumbaco administration obtained 30217 t/year and 1.22E-05 t/year, respectively.